Explaining the relationship between entrepreneurial learning and entrepreneurial ability through knowledge management perspective among undergraduate students base on SEM-PLS - Fu, Hongyan (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
How to improve the entrepreneurial ability of undergraduate students is an important issue that needs to be solved at present. From the perspective of knowledge management, this paper attempts to reveal the mechanism of transforming undergraduate students' entrepreneurial learning ability into entrepreneurial competence, and test the mediating and moderating theoretical model of the relationship between entrepreneurial learning, knowledge management, entrepreneurial atmosphere and entrepreneurial competence. Using Smart-PLS software, 182 questionnaires were analyzed; the results show that in terms of the relationship between entrepreneurial learning and entrepreneurial competence, undergraduate students’ knowledge management play a mediator role, the entrepreneurial atmosphere of universities play a moderator role.